Professional internship of social pedagogy students: new challenges and threats - Martincová, Jana; Staňková, Iva (Pedagogika Społeczna Nova, 2024)
The main objective of this study is to analyse the changes in social education professional internship for university students. We concentrated on identifying strengths and weaknesses of professional internship, and the opportunities and threats observed in the implementation of professional social education professional internship during the coronavirus crisis. We subsequently explain how the impacts of this extraordinary situation are reflected in the competency model of the future social educator. Due to the absence of specific research studies looking at the transformation of student professional internship during the coronavirus crisis period, we thought it seemed appropriate to investigate in detail one specific case, and use it to analyse the partial impacts of the pandemic in the implementation of the professional internship of specifically university students. Using a descriptive case study design, we analyze social education internships during the coronavirus period in the Czech Republic, utilizing student data (internship diary, facility assessment, self-assessment, and questionnaire) to identify changes in the internship system. We found many significant changes in the implementation of professional internship, which are fundamentally reflected in the competency model of Social Education graduate.